The Making of Modern Switzerland, 1848-1998
XIII, 163 p.
Keywords: A fascinating collection of essays by leading British and Swiss scholars which explore the development of Swiss democracy from 1848 to the present day. Culture and literature, politics and economics are looked at in turn in an attempt to unravel the extraordinary success of this microcosmic, multicultural society at the heart of Europe. The problem of contemporary Switzerland, faced with rapid changes within the European Union, are outlined with refreshing candour. The question is posed whether the country can retain its distinctive identity and traditional attitudes while at the same time seeking closer cooperation with the newly emerging Europe and accepting the challenges of the globalized economy.